Serum eotaxin level as a marker of atopic dermatitis severity in infants - V.A. Klymenko; O.M. Ashcheulov; O.V. Vуsotska; G.I. Pecherskaya (Zaslavsky O.Yu., 2017)
Background. Atopic dermatitis (AD) is a chronic inflammatory disease of the skin. The allergic skin inflammation is the heart of the clinical manifestation of AD. Eosinophils are one of the most significant effector cells of allergic inflammation. However, blood eosinophilia occurs only in some children with AD. In clinical practice at the present time, the activity of allergic inflammation is evaluated not only by the level of eosinophils, but also by concentrations of cytokines, one of which is eotaxin. The objective of the scientific work was to determine the role of eotaxin in the pathogenesis of AD. Materials and methods. The study involved 60 children aged 60 days to 3 years with clinical manifestations of AD during disease exacerbation (main group) and 36 healthy children (control group). Results. The median and interquartile intervals of serum eotaxin levels were established in mild (32.10 [16.05-41.86] pg/ml), moderate (33.5 [27.9-80.94] pg/ml) and severe (25.11 [18.14-54.42] pg/ml) AD. There were not found significant differences between groups and reference values of the control group (46.05 [27.9-61.4] pg/ml). There were isolated groups of patients with high (18 children - 50.2-189.78 pg/ml) and low (16 children - 2.79-19.54 pg/ml) eotaxin levels. The correlation was established between eotaxin levels and clinical features of AD: the total score on the SCORAD (Severity scoring of atopic dermatitis) scale (p = 0.01), the prevalence (p = 0.09), the total intensity of morphological manifestations (p = 0.01), redness (p = 0.01), lichenification (p = 0.01), swelling/papule (p = 0.06), oozing/crusting (p = 0.06), excoriation (p = 0.01), itching (p = 0.01) and sleep disorders (p = 0.01). It was found a possible increase in the number of CD3, CD4, CD8, CD16, CD22, CD25 lymphocytes, IgG and total IgE in the group of children with high eotaxin levels as compared to the patients with low eotaxin levels. Conclusions. Eotaxin is involved in the development of the AD acute phase and can be used as an objective severity marker of exacerbation.